Traces et espaces de consommation - Franck Cochoy; Jan Smolinski (Netcom)
The advent of mobile digital technologies has contributed to an evolution in the modalities of distribution and consumption. The present article focuses on the use of QR-codes, these two-dimensional barcodes which give every user equipped with a smartphone access to online content. They contribute to the Internet of Things and are thus an interaction between physical space and the digital universe. They also enable the gathering of digital traces that are meaningful not only for professionals but also for social sciences. Thanks to these traces, one can understand the new retail links developed between the physical space and the development of continuous information flows. From the analysis of these traces recorded during the visit of the QR-codes affixed on three food products (a packet of salt, a chocolate bar and a bottle of water), our investigation endeavours to make explicit the theoretical, methodological and analytical stakes involved in the process of digitising the space for physical retail mobility.